(3EjSGZhLis - (3GdeanqVd Hf YeQ Hf GdeaVd GdCHgQj GdSeQbfOj, CKjQ GdOjf,J (B663 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdYdGeI GaVd GdYdeGA GdeJCNQjf CKjQ GdOjf GdCHgQi s
(3BNQgG (B:s
(3ef ebOeGJ cGPHI THjgI HGdMb Ch HGdeTghQI Ch ef ebOeGJ hgejI cGPHI s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B279 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B315s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B206s
(3eUOQ GbJfGA GdCUd (B:s
(3GdXGgQjI (B(9304) s
Keywords: (3GdadSaI hGdefWbs